Occurrence, Density, and Transcriptomic Response of the Leafhopper Erythroneura sudra (Hemiptera: Cicadellidae) When Confronted With Different Fruit Tree Species. Issue 3 (28th June 2022) - Wang, Yueyue; Huang, Xunbing; Li, Hui; Chen, Guangyan
Abstract: The leafhopper, Erythroneura sudra (Distant) is becoming a dominant insect pest, and usually can cause significant damage to fruit production in northern China. We studied the occurrence and density of E. sudra on three fruit tree species and its transcriptomic responses when it was fed on leaves of these tree species. A higher density and survival rate of E. sudra were recorded when it fed on leaves of peach ( Amygdalus persica L.) (Rosales: Rosaceae) and cherry ( Cerasus pseudocerasus Lindl) (Rosales: Rosaceae) than on apple ( Malus domestica Mill) (Rosales: Rosaceae). Also, feeding on M. domestica induced the largest variation in transcriptomic profiles in E. sudra . In total, 166 genes were differentially expressed (89 upregulated and 77 downregulated) in E. sudra when it fed on M. domestica, compared to when it fed on the other two tree species. The upregulated genes were mainly related to 'response to oxidative stress', 'stress-resistance', and 'xenobiotic metabolic process'. The downregulated genes were mainly related to 'structural constituent of cuticle', 'biosynthetic process', and 'development regulation'. These results suggested that M. domestica significantly changed the expression of many genes and consequently caused lower occurrence and density of E. sudra . Such information could enhance our understanding of the leafhopper–host plant relationship. Additionally, it can contribute to the improvement of current control strategies for this pest.